The Implementation of Scaffolding Technique in Teaching English to The Students of High Schools in Semarang –A Case Of High School English Teachers in Semarang - Hayati, Nesti Noor; Sutopo, Djoko; Faridi, Abdurrachman (English Education Journal, 2019)
The use of appropriate teaching technique to teach English in senior high schools in the context of EFL determines the quality of the students’ achievement because the success of their efforts to reach the learning goals cannot be separated from teacher’s role in assisting the process of learning.The research was conducted to describe the implementation of scaffolding technique in 6 senior high school in Semarang and to analyze the obstacles and factors underlying found in the process of the implementation used in the classroom by applying Dewerianka’s scaffolding model.The data were taken from classroom interactions of 6 teachers in 6 public senior high schools in Semarang. The research subjects were 6 English teachers and 10th grade students in 6 different public schools. There were four stages of scaffolding technique suggested by Dewerianka, they were building the field, modeling, joint construction, and independent construction. The result shows that the implementation of scaffolding technique contributes to the students’ ability. It was seen on (a) the students were able to produce the text depending on the purpose, social contexts, and medium in oral or written forms and (b) the teacher gave the contribution during individual work and reduced the contribution during pair work or group work. The strengths of the scaffolding technique in teaching English for 10th grade students are (a) to build the character of the students, and (b) to measure the ability of the students when producing the texts. Meanwhile, the obstacles were: (a) the differences of characters and ability among students, (b) limited time allotment for English class, and (c) school facility. This research will be beneficial as the source of information and reference related to the English teaching in EFL context.